The effect of nitrate and phosphate availability on Emiliania huxleyi (NZEH) physiology under different CO2 scenarios - Rouco, Mónica; Branson, Oscar; Lebrato, Mario; Iglesias-Rodriguez, M. Débora (Frontiers in Microbiology, 2013)
Growth and calcification of the marine coccolithophorid Emiliania huxleyi is affected by ocean acidification and macronutrients limitation and its response varies between strains. Here we investigated the physiological performance of a highly calcified E. huxleyi strain, NZEH, in a multiparametric experiment. Cells were exposed to different CO2 levels (ranging from 250 to 1314 µatm) under three nutrient conditions [nutrient replete (R), nitrate limited (-N) and phosphate limited (-P)]. We focused on calcite and organic carbon quotas and on nitrate and phosphate utilization by analyzing the activity of nitrate reductase (NRase) and alkaline phosphatase (APase), respectively. Particulate inorganic (PIC) and organic (POC) carbon quotas increased with increasing CO2 under R conditions but a different pattern was observed under nutrient limitation. The PIC:POC ratio decreased with increasing CO2 in nutrient limited cultures. Coccolith length increased with CO2 under all nutrient conditions but the coccosphere volume varied depending on the nutrient treatment. Maximum APase activity was found at 561 µatm of CO2 (pH 7.92) in -P cultures and in R conditions, NRase activity increased linearly with CO2. These results suggest that E. huxleyi’s competitive ability for nutrient uptake might be altered in future high-CO2 oceans. The combined dataset will be useful in model parameterizations of the carbon cycle and ocean acidification.